Radar altimetry measurements over antarctic ice sheet: A focus on antenna polarization and change in backscatter problems - Remy, F.; Flament, T.; Blarel, F.; Benveniste, J. (Advances in Space Research, 2012)
ISI Document Delivery No.: 010LG Times Cited: 1 Cited Reference Count: 25 Cited References: Arthern RJ, 2001, J GEOPHYS RES-ATMOS, V106, P33471, DOI 10.1029/2001JD000498 Brenner AC, 2007, IEEE T GEOSCI REMOTE, V45, P321, DOI [10.1109/TGRS.2006.887172, 10.1106/TGRS.2006.887172] Davis CH, 2004, IEEE T GEOSCI REMOTE, V42, P2437, DOI 10.1109/TGRS.2004.836789 DAVIS CH, 1993, J GLACIOL, V39, P687 FUNG AK, 1982, IEEE T GEOSCI REMOTE, V20, P528, DOI 10.1109/TGRS.1982.350421 Lacroix P, 2009, REMOTE SENS ENVIRON, V113, P2633, DOI 10.1016/j.rse.2009.07.019 Lacroix P, 2008, REMOTE SENS ENVIRON, V112, P1712, DOI 10.1016/j.rse.2007.08.022 Legresy B, 1999, GEOPHYS RES LETT, V26, P2231, DOI 10.1029/1999GL900531 Legresy B, 1998, J GLACIOL, V44, P197 Legresy B, 2005, REMOTE SENS ENVIRON, V95, P150, DOI 10.1016/j.rse.2004.11.018 Li J., 2002, INT S PHYS MECH PROC, P233 Li J, 2004, ANN GLACIOL, V38, P309, DOI 10.3189/172756404781814988 Matzler C., 1987, Remote Sensing Reviews, V2 Pritchard HD, 2009, NATURE, V461, P971, DOI 10.1038/nature08471 Remy F, 2009, REMOTE SENS-BASEL, V1, P1212, DOI 10.3390/rs1041212 Remy F, 2006, IEEE T GEOSCI REMOTE, V44, P3289, DOI 10.1109/TGRS.2006.878444 RIDLEY JK, 1988, INT J REMOTE SENS, V9, P601 Tran N, 2008, IEEE T GEOSCI REMOTE, V46, P3694, DOI 10.1109/TGRS.2008.2000818 Vincent P, 2006, SENSORS-BASEL, V6, P208, DOI 10.3390/s6030208 Wingham D., 2009, GEOPHYS RES LETT, V36 Wingham DJ, 2006, PHILOS T R SOC A, V364, P1627, DOI 10.1098/rsta.2006.1792 Wingham DJ, 2006, ADV SPACE RES-SERIES, V37, P841, DOI 10.1016/j.asr.2005.07.027 Wingham DJ, 1998, SCIENCE, V282, P456, DOI 10.1126/science.282.5388.456 Zwally HJ, 2005, J GLACIOL, V51, P509, DOI 10.3189/172756505781829007 Zwally HJ, 2002, J GLACIOL, V48, P199, DOI 10.3189/172756502781831403 Remy, F. Flament, T. Blarel, F. Benveniste, J. 1 ELSEVIER SCI LTD OXFORD ADV SPACE RES In this paper, we investigate the impact of the error due to the penetration of the altimetric wave within the snowpack. The phenomenon has two different impacts. The first one, due ...